2013
DOI: 10.1111/aogs.12136
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and endothelial markers in postmenopausal women taking oral or transdermal hormone therapy

Abstract: Reduced levels of soluble E-selectin in women using menopausal hormone therapy could lead to reduction in the intensity of expression of the adhesion factors on the surface of the vascular endothelium. Menopausal hormone therapy might have advantageous effects on vascular endothelial function through adiponectin. Transdermal therapy may have adverse effects associated with elevated tissue activator plasminogen antigen levels and thereby the higher risk of ischemic heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…This lack of effect of more prolonged estrogen treatment on adiponectin levels in women has been confirmed elsewhere (Nishizawa et al, 2002;Ibanez and de Zeghe, 2004;Sumino et al, 2004). In contrast, increases (Chu et al, 2006a, b;Ruszkowska et al, 2013) as well as decreases (Im et al, 2006) in adiponectin levels in post-menopausal women have been observed after prolonged estradiol administration. Hence, further investigation is needed to clarify the relationship between sex steroids and circulating adiponectin levels.…”
Section: Adiponectinsupporting
confidence: 52%
“…This lack of effect of more prolonged estrogen treatment on adiponectin levels in women has been confirmed elsewhere (Nishizawa et al, 2002;Ibanez and de Zeghe, 2004;Sumino et al, 2004). In contrast, increases (Chu et al, 2006a, b;Ruszkowska et al, 2013) as well as decreases (Im et al, 2006) in adiponectin levels in post-menopausal women have been observed after prolonged estradiol administration. Hence, further investigation is needed to clarify the relationship between sex steroids and circulating adiponectin levels.…”
Section: Adiponectinsupporting
confidence: 52%
“…As with leptin and ghrelin, and effect of HT on adiponectin is varied, likely because of different HT formulations in different populations. Several studies show increased adiponectin levels in women taking HT (Christodoulakos et al, 2008; Ruszkowska et al, 2013), whereas one study reported decreased adiponectin levels with HT (Im et al, 2006). …”
Section: Estrogen Regulation Of Whole-body Metabolismmentioning
confidence: 99%